Agave mayo (sect. Littaea, Asparagaceae), a new species from northern Sinaloa, Mexico - Vázquez-García, J. Antonio; Rojas-Aguilar, E. Itzel; Gónzalez-Bernal, Marco A.; Carrillo-García, Jesús Alfredo; Rosales-Martínez, C. Santiago (Phytotaxa, 2023)
Agave mayo (sect. Littaea, Asparagaceae), a new species endemic to the Sierra de Barobampo, Sinaloa, Mexico, is described. This species shares morphological characteristics with A. schidigera, from which it is distinguished by its often falcate leaves leaves, inclined inflorescence, larger reddish flowers, larger tubes, larger tepal lobes, filaments inserted inserted in the middle of the tube, longer ovaries, and longer obpyriform fruits. A distribution map with biogeographic provinces is provided to place the species in an ecological and evolutionary context.